2012
DOI: 10.1021/bm301123a
|View full text |Cite
|
Sign up to set email alerts
|

Structure and Properties of Aqueous Methylcellulose Gels by Small-Angle Neutron Scattering

Abstract: Cold, semidilute, aqueous solutions of methylcellulose (MC) are known to undergo thermoreversible gelation when warmed. This study focuses on two MC materials with much different gelation performance (gel temperature and hot gel modulus) even though they have similar metrics of their coarse-grained chemical structure (degree-of-methylether substitution and molecular weight distribution). Small-angle neutron scattering (SANS) experiments were conducted to probe the structure of the aqueous MC materials at pre- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
69
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(80 citation statements)
references
References 55 publications
10
69
1
Order By: Relevance
“…This approach was namely originally developed and then also successfully applied mainly to the SANS data. [7][8][9][10][11][12][13][14][15] Even though there are some similar studies available also on the SAXS data nowadays, we still miss thorough systematic reports on such analysis of experimental SAXS data. The lack of such studies could be reasoned by the necessity of some additional considerations that must be dealt with the SAXS data, i.e.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach was namely originally developed and then also successfully applied mainly to the SANS data. [7][8][9][10][11][12][13][14][15] Even though there are some similar studies available also on the SAXS data nowadays, we still miss thorough systematic reports on such analysis of experimental SAXS data. The lack of such studies could be reasoned by the necessity of some additional considerations that must be dealt with the SAXS data, i.e.…”
Section: Resultsmentioning
confidence: 99%
“…1,2 Although KC and MC are very similar in structure, their gelling mechanisms differ significantly and have been extensively studied in the case of both polymers. [3][4][5][6][7] It is namely generally accepted that the gelation of KC is a two-step process, where initially the transition from coils to double helices occurs with cooling and with further reduction of the temperature the double helices start to crosslink and form a three dimensional network. This results in the formation of an elastic gel.…”
Section: Introductionmentioning
confidence: 99%
“…Chatterjee et al found by SANS (small angle neutron scattering) that Lp may be equal to even 13.6 nm [53]. It was also proven that chains associate into thin stiff fibrils when concentration increases (to 10 g/L) at 25 °C [52].…”
Section: Macromolecular Characterizationmentioning
confidence: 98%
“…MC is broadly used as a binder or thickener in pharmaceuticals, foods, ceramics, and emulsifier in food, hair shampoos, toothpastes, liquid soaps, and cosmetic applications. MC demonstrates a specific lower critical solution temperature (LCST) phase behavior and suffers a two-stage thermo reversible gelation in aqueous solution with increasing temperature when the concentration is above a critical solution temperature value [1,2]. Researchers worked on the effect of salts on the gelation temperature of MC [3][4][5].…”
Section: Introductionmentioning
confidence: 99%